WebCultura: do método à arquitetura no ambiente digital - Toledo Filho, João Cesar Lopes (2008)
This project aims at narrowing the gap between the researcher of new technologies and the possibility of production of on-line knowledge, which is related to technological resources, hardware, structure of virtual content and the design of interfaces. This study is based on the methodology of project for digital environment, which is discussed and analyzed as fundamental stage in the development of the site:<www.webcultura.com.br>. So, Virtualisation brings about a discussion that concerns the production in the digital environment. It does not seek for answers concerning technology, but it proposes a search for broader and wider possibilities, concerning the way we think about the development of knowledge. The collective intelligence is an ongoing renovation, which might be relevant to any kind of language, what includes hypermedia. For those who intend to develop network knowledge, the largest challenge is dependent of an unity, which means to change the production of a hypermedia to montage and hybrid composition of materials properly selected, organized, indexed and remixed, translated into digital interfaces. Therefore, this piece of research tries not only to this discussion as well as propose new transformative innovating and critical pathway on new media.